2002
DOI: 10.2337/diacare.25.10.1704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Oil Versus Corn Oil Supplementation on LDL and HDL Subclasses in Type 2 Diabetic Patients

Abstract: OBJECTIVE—The increased risk of coronary heart disease associated with type 2 diabetes may be partially explained by dyslipidemia characterized by high plasma triacylglycerol (TAG), low HDL cholesterol, and a predominance of atherogenic small dense LDLs. Fish oil reduces plasma TAG and has previously been shown to improve the distribution of LDL subclasses in healthy subjects and might, therefore, be a good nonpharmacological treatment for type 2 diabetic patients. In the present study, we investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 21 publications
4
41
2
Order By: Relevance
“…Others have reported no effect of n-3 FA in subjects with type II diabetes (Luo et al, 1998) or a tendency to a smaller increase than in a control group (Petersen et al, 2002). Reduction of small HDL was observed in one report, but this effect was seen only with intervention of EPA, not with DHA (Woodman et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Others have reported no effect of n-3 FA in subjects with type II diabetes (Luo et al, 1998) or a tendency to a smaller increase than in a control group (Petersen et al, 2002). Reduction of small HDL was observed in one report, but this effect was seen only with intervention of EPA, not with DHA (Woodman et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…The reductions of VLDL size and reduced concentration of large VLDL that we observed have, to our knowledge, not been previously reported. Others have reported no change in the distribution of VLDL subclasses in subjects with type II diabetes (Patti et al, 1999) or did not measure these subclasses (Petersen et al, 2002). Reduction of VLDLcholesterol, on the other hand, is well documented but mainly in the setting of a concomitant lowering of triglycerides (Harris et al, 1983;Malasanos and Stacpoole, 1991;Connor, 2000;Montori et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trials included in the pooled analyses were small, with a median of 23 patients. Seventeen of the published papers were duplicate publications of six trials [22, 27, 33, 34, 36-38, 40, 42-46, 48, 51, 54, 55]; multiple papers for each trial are indicated by the following grouping of references: [22,38], [27,34,36,37], [40,54,55], [42,48,51], [43,46], [44,45]. There was sufficient information on only 12 of the 98 outcomes to allow data to be pooled, the results of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). Four trials reported changes in HDL-3 among 114 nonhypertriacylglycerolaemic subjects [32,46,47,54]. n-3 PUFA supplementation non-significantly decreased HDL-3 by 0.02 mmol/l (95% CI −0.07 to 0.03; p=0.42) (ESM Fig.…”
Section: Resultsmentioning
confidence: 99%